Persepsi Guru Tentang Pemeliharaan Sarana Pembelajaran di SMKN 8 Padang - Riska Ekfinofriza; Syahril Syahril; Anisah Anisah; Sulastri Sulastri (Journal of Educational Administration and Leadership, 2021)
This research is descriptive quantitative. The population of this study were 54 productive teachers at SMKN 8 Padang. The technique used is Simple Random Sampling. The number of samples obtained was 35 teachers. The research instrument in the form of a questionnaire using a Likert scale measurement. The results showed that the maintenance of learning facilities at SMKN 8 Padang that 1) routine / continuous maintenance was good with a score of 4.08; 2) Periodic maintenance is good with a score of 3.58; 3) Incidental maintenance is good with a score of 3.95; 4) Preventive maintenance is classified as good with a score of 3.82.